Fibrinolysis: Mathematical and Experimental Studies - Liniger, W; Ruegsegger, P (Thrombosis and Haemostasis, 1967)
In the present paper we discuss a mathematical model of fibrinolysis, encompassing the major chemical reactions associated with this process, and show that it is in good agreement with the results of extensive experimental studies. We anticipate that such mathematical simulation, possibly combined with automation of auxiliary experimental measurements, may serve as a basis for faster and simpler clinical assays.